The International Biotechnology Industry: A Dynamic Capabilities Perspective - Madhok, Anoop; Osegowitsch, Thomas (Journal of International Business Studies, 2000)
This paper extends our understanding of the diffusion of technology across firms and nations. The dynamic capabilities perspective in its micro and macro version provides the theoretical framework for an explanation of the international organization of the biotechnology industry. We address two interrelated aspects of the phenomenon of international diffusion: organizational form and geographical flows. An examination of the empirical profile lends support to the dynamic capabilities argument.